Effect of fish to starch ratio on viscoelastic properties and microstructure of fish cracker ('keropok') dough - Kyaw, Z. Y.; Yu, S. Y.; Cheow, C. S.; Dzulkifly, M. H.; Howell, N. K. (Wiley, 2001)
Starch granules found at the centre of fish crackers ('keropok') which contained from 0 to 10% fish did not gelatinize after 2 h steaming. This was because of water movement from the centre to the periphery during steaming. A fish protein network started to develop in dough with a 15% fish content and this entrapped water molecules. These water molecules helped to complete gelatinization. The viscoelastic properties of 'keropok' dough increased with an increasing fish to starch ratio and also because of the formation of a fish-protein network in the dough.